Marine shrimp rearing in fresh water in different stocking densities - Fonseca, Sthelio Braga da; Mendes, Paulo de Paula; Albertim, Cândida Juliana de Lyra; Bittencourt, Cláudio Figueiroa; Silva, José Humberto Vilar da (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of stocking density in Litopenaeus vannamei rearing in fresh water. The evaluated densities were: 5 (D5), 10 (D10), 15 (D15), 20 (D20), 25 (D25) and 30(D30) shrimp per square meter. The experimental design was completely randomized, with two replicates. The performance of shrimp and the physical and chemical parameters of water were evaluated. Mathematical models were generated to estimate the zootechnical parameters of L. vannamei. The mean alkalinity of water was 36.8±3.06 mg L-1, and the mean hardness was 38.21±3.07 mg L-1. At 52 days of rearing, treatment D5 had the best results on weight (5.40±0.99 g) and length (9.50±0.20 cm), but the weight did not differ significantly from treatments D10, D15 and D25. Treatment D25 had the best shrimp survival rate (72.10±9.3%). Based on the mathematical models of weight and length as function of rearing time, it was found that higher stocking densities provide shrimp with less weight and length gain.